(untitled) (International Journal of Studies in Nursing, 2022)
Objective: To explore the effect of nursing record sheet and operation registration form in daytime ophthalmic surgery. Methods: the nursing record sheet and operation registration form of daytime ophthalmic surgery were designed and used to evaluate the incidence of adverse events and the satisfaction of doctors in the operating room before and after use. Results: from January 2018 to June 2019, there were 15 adverse events caused by unclear handover, wrong record, wrong eye classification, wrong application of antibiotics and waiting for surgical consumables in ophthalmology due to nursing record, with an incidence of 3.71%;From July 2019 to December 2020, there were only 2 cases of ophthalmic defects caused by the record sheet, with an incidence of